Metaphor and social action: how worker attention is translated into capital. Issue 1 (1st January 2019) - Roderick, Ian
ABSTRACT: Using the example of attention, this paper argues that there is a tendency to treat conceptual metaphors as representational resources at the expense of critically examining how they are implicated in the material structuring of social action. Rather than understanding metaphor in terms of transference, it is proposed that the concept of translation be applied to how we theorise the workings of metaphor. By translating rather than merely transferring concepts from one domain to another, metaphors function as semiotic materialisations that give structure to social action. It is through metaphor that human attentional processes are made to be translated into the material practices of knowledge work under cognitive capitalism. However, for attention to be translated from cognitive process into labour more than a simple associative process must take place. The attention-as-labour metaphor does not just transform how we think about work, it lends itself to transforming how work is performed and managed. In this way, as discursive resources metaphors participate in the constitution not only of our understanding of social realities but also how we build and act within those realities. Thus, metaphors are not just evidence of asymmetries in power relations but also function as instruments of those asymmetries.